2017
DOI: 10.5415/apallergy.2017.7.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to ticagrelor and low response to clopidogrel: a case report

Abstract: Ticagrelor is widely used to treat acute coronary syndrome. Hypersensitivity reaction of ticagrelor is rarely recognized. A low response to clopidogrel, which occurs in up to 23% of patients, is an independent risk factor for stent thrombosis. Management of patients with a low response to clopidogrel and ticagrelor hypersensitivity who are undergoing antithrombotic therapy remains to be a challenge. Herein, we report a patient with low response to clopidogrel and ticagrelor hypersensitivity, who was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
8
0
2
Order By: Relevance
“…Hypersensitivity skin reactions to ticagrelor are relatively rare [ 6 , 10 ]. To the authors' knowledge, there are currently less than 40 reported hypersensitivity skin reactions with ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypersensitivity skin reactions to ticagrelor are relatively rare [ 6 , 10 ]. To the authors' knowledge, there are currently less than 40 reported hypersensitivity skin reactions with ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity skin reactions to ticagrelor are exceedingly rare, with less than 40 cases reported by the United States Food and Drug Administration (FDA) [ 6 ]. The index case was described by Quinn et al in 2014 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ticagrelor hypersensitivity can be either immediate type or delayed type. Desensitization attempts without fully establishing the underlying pathology can be detrimental [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, en caso de que se presente reacción con otro de los nuevos antiagregantes ya nombrados, una buena alternativa es la desensibilización o incluso el uso de otros medicamentos, incluidos los anticoagulantes orales, que tienen menor evidencia clínica en dicho contexto. 5 Es de importancia clínica conocer las reacciones adversas poco frecuentes de algunos medicamentos, en especial los antiagregantes plaquetarios que en el contexto de síndrome coronario agudo son el pilar del manejo. Los reportes de caso nos pueden dar pautas para el diagnóstico y tratamiento.…”
Section: Preprintunclassified
“…4 De esta manera, en el presente reporte de caso documentamos un evento raro de reacción de hipersensibilidad a dicho medicamento, con pocos informes a nivel mundial. 5 En los casos leves el diagnóstico ha sido solo clínico, salvo un caso de reacción severa con dermatosis neutrofílica febril aguda que requirió biopsia. 3 El primer caso publicado mostró infiltrado linfocítico.…”
unclassified